Fighting against drug-resistant tumors by the inhibition of γ-glutamyl transferase with supramolecular platinum prodrug nano-assemblies. Issue 22 (1st June 2021) - Wang, Lina; Liu, Zejun; He, Shumei; He, Shasha; Wang, Yupeng
Abstract : Supramolecular Pt-CD/Dex-Ad@OU nano-assemblies for suppressed expression of GGT and breaking the intracellular redox balance to improve the efficacy on cisplatin-resistant human pulmonary carcinoma A549 models. Abstract : Pt(ii )-based antitumor drugs ( e.g. cisplatin and oxaliplatin) are one of the most successful and frequently used drugs in cancer chemotherapy at present. However, drug resistance and severe side effects are the major problems in the application of platinum drugs. Detoxification of Pt(ii ) drugs is one of the most important mechanisms of drug resistance. Herein, a supramolecular Pt(iv ) prodrug nano-assembly delivery system is designed and used to encapsulate a γ-glutamyl transferase (GGT) inhibitor (OU749) (Pt-CD/Dex-Ad@OU nano-assemblies) for the synergistic chemotherapy of cisplatin-resistant cancer. Pt-CD/Dex-Ad@OU nano-assemblies could be efficiently taken up by cisplatin-resistant cancer cells and release a drug in the intracellular reductive environment. The Pt-CD/Dex-Ad@OU nano-assemblies can efficiently suppress the expression of GGT, depleting GSH and augmenting ROS via the reduction of the Pt(iv ) prodrug. Thereby, by breaking the redox balance the detoxification and antiapoptosis mechanisms of Pt(ii ) drugs can be overcome. Thereafter, the excellent therapeutic efficacy of Pt-CD/Dex-Ad@OU nano-assemblies is validated on a cisplatin-resistant human non-small cell lung cancer (A549/DDP) model. Furthermore, the inhibition of GGT protein is expected to reduce the nephrotoxicity of cisplatin. Collectively, this study provides a promising strategy to break the redox balance for overcoming drug resistance and maximizing the efficacy of platinum-based cancer therapy.